The confidential enquiry into maternal deaths in South Africa: a case study. (September 2014) - Moodley, J; Pattinson, RC; Fawcus, S; Schoon, MG; Moran, N; Shweni, PM; ,
Abstract : The Confidential Enquiry into Maternal Deaths (CEMD) in South Africa has been operational for 15 years. This case study describes the process of notification and independent assessment of maternal deaths, predominantly in facilities. In the earlier years of the Enquiry, institutional maternal mortality ratio increased and was 176.2 per 100 000 live births in the 2008–10 triennium; thereafter it decreased to 146.7 in the 2011/12 period. The slow progress was due to the significant contribution of HIV/AIDs to maternal mortality and challenges in implementing the recommendations that were devised from the findings of the Enquiry. Nevertheless, the CEMD process has been maintained and strengthened so it is currently able to perform routine maternal death surveillance at both national and district levels, identify deficiencies within the health system, generate reports and also provide early warning about alarming trends such as the increasing numbers of deaths due to caesarean‐section‐associated haemorrhage.